South Africa's policy on civilian participation in post conflict peace building: Burundi 2001-2008 - Mtshali, Nozizwe Lucia (My University, 2014)
The South African policy for peace missions is found in the 1999 “White Paper on South African Participation in International Peace Missions” of the Department of International Relations and Cooperation1. The White Paper adopts a comprehensive approach for the creation of peace in conflict and post conflict societies. The comprehensive approach includes the employment of military and civilian actors. Activities of these actors are determined by the nature of the peace mission which includes preventative diplomacy, peace making, peace building, peace enforcement, humanitarian assistance and humanitarian intervention. The policy further promotes the strategy of South African actors addressing the underlying causes of conflict instead of symptoms. The research seeks to investigate whether or not South African institutions implement the civilian peacebuilding aspect of the policy and adopts the use of the Burundi peace mission (2000-2008) as a case study. Qualitative research, which includes the use of document research and personal interviews, is the adopted research methodology. Through application of the variables of the 5-C protocol (coalitions and clients, commitment, capacity, context and content) the research established several implementation challenges. The research also utilised the 5-C protocol variables for recommendations on possible reforms.
Keywords: Peacebuilding; Burundi; Policy; South Africa; Peace missions; Foreign relations